Does Harboring Terrorists Have Economic Costs? - Claude Berrebi; Esteban F. Klor (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
The literature on conflict and terrorism has paid little attention to the economic costs of terrorism for the perpetrators of terror attacks. Our research fills that gap by examining the economic costs of harboring suicide terror attacks. We combine data on Palestinian suicide terrorists with data from the Palestinian Labor Force Survey, to identify and quantify the impact of a successful attack on unemployment and wages. We find robust evidence that terror attacks have important economic costs. They cause a significant increase in unemployment and a significant decrease in wages and on the number of Palestinians working in Israel. Importantly, these effects are persistent and last for at least six months after the attack.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330